FUNGSI INVESTASI DALAM PERSPEKTIF EKONOMI ISLAM: The Function of Investment in the Perspective of Islamic Economics - Siti Sholikhatunnisa; Hasan, Asyari; Alvadia R, Wirdaning; Fachrini, Ariva; Dwi Putri, Nazwa (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
Abstract: This research provides an overview of the function of investment from the perspective of Islamic and conventional economics. The purpose of this research is to understand the function of investment in the perspective of conventional economics, the purpose of investment in the perspective of Islamic economics, and how the function of investment compares in the perspectives of conventional and Islamic economics. The methodology used in this research is Library Research (literature review) and critical thinking by the author. The review in this research is based on literature and relevant writings related to the main topic of this research, which states that investment is the act of allocating funds or other resources at present, with the aim of obtaining future profits. The function of investment in the conventional perspective is the relationship between investment levels and national income levels that form a curve. The types of investment in the conventional economic perspective are categorized as direct investment and indirect investment. In the function of investment from the conventional economic perspective, it is determined by interest rates, while in the function of investment from the Islamic economic perspective, it is based on the teachings and commandments of paying zakat for productive wealth. Investment in the perspective of Islamic economics serves as a means to achieve social and moral goals, one of which is through zakat, infaq, and sedekah. This concept emphasizes the importance of sharing with the community and helping to address issues of poverty and social inequality. Keywords: : Investment Function, Economics, Conventional, Islam, Sharia Principles Abstrak: Penelitian ini memberikan gambaran tentang fungsi investasi dalam perpektif ekonomi islam serta ekonomi konvensional. tujuan dilakukannya penelitian ini buat mengenali fungsi investasi dalam perspektif ekonomi konvensional, guna investasi dalam perspektif ekonomi islam serta gimana perbandingan fungsi investasi dalam perspektif ekonomi konvensional serta islam. tata cara yang digunakan dalam riset ini merupakan tata cara Library Research (kajian pustaka) serta pula pemikiran kritis dari penulis. ulasan dalam riset ini Bersumber pada literatur serta sebagian tulisan relevan dengan pokok ulasan hasil riset ini kalau investasi ialah aksi mengalokasikan dana ataupun sumber energi yang lain pada dikala ini, dengan tujuan buat mendapatkan keuntungan di masa depan. fungsi investasi dalam perspektif konvensional ialah keterkaitan tingkatan investasi serta tingkatan pemasukan nasional yang membentuk sesuatu kurva.jenis investasi dalam perspektif ekonomi konvensional dibedakan menjadi investasi langsung serta investasi tidak langsung. pada fungsi investasi perspektif ekonomi konvensional didetetapkan oleh suku bunga, sebaliknya pada fungsi investasi perspektif ekonomi islam dilatarbelakangi oleh landasan ajaran perintah membayar zakat untuk yang mempunyai peninggalan produktif. investasi dalam perspektif ekonomi islam ialah perlengkapan buat menggapai tujuan-tujuan sosial serta moral salah satu triknya lewat zakat, infaq serta sedekah. Konsep ini menekankan berartinya berbagi dengan masyarakat, membantu menanggulangi permasalahan kemiskinan serta kesenjangan sosial. Kata Kunci: Fungsi Investasi, Ekonomi, Konvensional, Islam, Prinsip Syariah